Soil Characteristics as Influenced by Closure of Forests of Bundelkhand Division and the Native Vegetation Associated with It - Singh, Dashrath; Srivas, N. C.; Mannikar, N. D. (Indian Forester, 1983)
Soil fertility with respect to available nitrogen. Phosphorus and potash and some important site characteristics of the Bundelkhand forest soils were studied. These studics revealed that the Bundelkhand forest soils are rich in org.nic carbon. Indicating their high available nitrogen status. Most of the soils are slightly acidic in reaction and rich in available phosphorus. With the protection of forests against human and anima1 interference after felling. High organic matter accumulations were observed. Thus, the closure of these forests resulted in increased soil fertility which increased further with its duration Teak forests are found on acid to near neutral soils, rich in organic matter and nitrogen (C/N ratio 11 to 19). Trees of Genera anogeissus are quite common in these forests. A. pendula appears to be occurring on sites relatively poor in C/N ratio than that for A. latifoila. Amongst herbaceous vegetation Aristida is the most common one followed by Sporoboills and Oropetium. Aristida, the dominant grass Species of Bundelkhand forest, has shown adaptability to varying site characteristics.